Endoscopic Management of Pancreatic Injury Due to Abdominal Trauma - Bhasin, Deepak Kumar; Rana, Surinder Singh; Rao, Chalapathi; Gupta, Rajesh; Verma, Ganga Ram; Kang, Mandeep; Nagi, Birinder; Singh, Kartar (JOP. Journal of the Pancreas, 2012)
Context There is limited experience with pancreatic endotherapy in patients with pancreatic injury due to trauma. Objective To retrospectively evaluate our experience of endoscopic management of pancreatic trauma. Patients Eleven patients (10 males and 1 female; mean age: 21.8±11.9 years) with pancreatic trauma. Intervention Endoscopic therapy. Patients with pseudocyst and a gastroduodenal bulge were treated with endoscopic transmural drainage. Pseudocysts without bulge or patients with external pancreatic fistula were treated with transpapillary drainage. Results Seven patients (6 males, 1 female) were treated for symptomatic pseudocyst and 4 patients (all males) were treated for persistent external pancreatic fistula. Three patients with external pancreatic fistula had partial disruption of pancreatic duct (head: 2 cases; tail: 1 case) and were successfully treated with bridging pancreatic stent (2 cases) or bridging nasopancreatic drain (1 case) with resolution of external pancreatic fistula in 4 to 6 weeks. Of seven patients presenting with symptomatic pseudocyst (size range: 4-14 cm), two patients were successfully treated with cystogastrostomy and there has been no recurrence over a follow up of 20 and 16 months, respectively. Five patients underwent transpapillary drainage. Three patients had partial disruption and two had complete disruption. In the former, a bridging nasopancreatic drain was placed in one patient and stent in two patients. All three patients had resolution of pseudocyst within 8 weeks and there has been no recurrence over a follow-up of 11 to 70 months. In two patients with complete disruption, non-bridging stent did not resolve the pseudocysts and required surgery. Conclusion Pancreatic injury due to trauma can be effectively treated endoscopically.